A legal comparative study between Malaysia and Australia on the hygiene level of food production / Johana Baidura Putri Johari…[et al.] - Johari, Johana Baidura Putri; Abd Halim, Noorelynna Hanim; Mohd Shafie, Nurul Syafiqah; Mohd Khalid, Sarah Yasmin (2011)
There are few types of laws that govern hygiene level of food production. In Malaysia there is the Malaysian Food Act 1983 which is the Parent Act and under it there is Malaysian Food Regulations 1993 and Malaysian Food Hygiene Regulations 2009. There are also similar laws that exist in Australia which is Food Standards Australia New Zealand 1991 and Australian Food Safety Standard 3.2.3. which is under Australia New Zealand Food Standards. However, although it is similar, there are many differences that can be seen in the Malaysian food law. This study is done to compare between the laws in Malaysia and Australia in order to improve hygiene level in Malaysia so that it is at the same par as hygiene levels in Australia. In addition, it is to give proper awareness to consumers on the importance of food hygiene.